An economic study of banana production by BKB borrowers in a selected area of Sylhet district of Bangladesh - Samadder, Anusree; Rahman, Mohammad Ataur; Saha, Jiban Krishna (Fundamental and Applied Agriculture, 2017)
Banana farming is a capital-intensive agribusiness initiative in Bangladesh. Success of banana cultivation largely depends on precise use of inputs in exact times and adequate quantity. So, sufficient and uninterrupted credit support is essential for this type of investment. The present study examined the adequacy, utilization and repayment of credit, the profitability and major problems of banana cultivation in Fenchuganj upazila of Sylhet district in Bangladesh. Primary data were collected from 60 borrowers of Bangladesh Krishi Bank (BKB) who were engaged in banana cultivation. Both tabular and econometric techniques were used to analyze the collected data. The findings of this study revealed that the adequacy of the loan was satisfactory. Borrowers were found to be acquainted about purposive utilization of loaned money. Most of the credit amount (92.64%) was utilized for farming purposes. Status shows that repayment was fully satisfactory (100%). Multiple regression model indicates that amount of loan received, savings, age, and return from production were significantly affecting loan repayment. The total cost of production of banana was estimated Tk. 240371 per acre, while gross and net returns were Tk. 331221 and 90850, respectively. The BCR was 1.38 indicating that 1 Tk. investment resulted in a net benefit of Tk. 0.38. Finally, the study identified some major problems of banana cultivation like lack of human labor, low output price, high prices of inputs, lack of quality sucker, and lack of storage facilities etc. As lack of human labor is the most chronic problem faced by the banana growers, capital intensive modern technology should be employed in banana cultivation and for that institutional credit facilities should, therefore, be made available on easy terms and conditions to the banana growing farmers.